6 - Scolarisation – Travail et Genre en Algérie - Houria, Sadou (Africa Development, 2007)
This article focuses on education, work and gender to reflect on several statis- tical data and the experience of women in Algeria. Generally, statistical data on the evolutionary trends on children’s education in Algeria shows that the de- mocratisation of education has succeeded in increased enrolment in primary, secondary and university education. Several studies also reveal that, on the aver- age, girls performed better than boys due to the fact that education represents for girls the only gateway to the outside world, in particular to the world of work, and as a means to escape family restrictions and rise above the situation of women. In addition the employment of women remains marginal. In an estimated population of 14.5 million, less than one million women participate in paid work force. The employment of women remains linked to their matrimonial situation. Women are encouraged in sectors such as education, health and public services, thus reflect- ing the basis of division of labour by gender. The article concludes that although the statistics show progress, it cannot show the processes of significant differ- ences in gender discrimination. What would be of interest is how girls and boys occupy the spaces of learning and that of work. How are power relations between girls and boys in these spaces structured? How does the position occupied by the two groups influence sexual identities?.